Forensic Assistance Project: Consultant Report 1999-025 Trnovo I Republika Srpska Commission on Tracing Prisoners and Missing Persons - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Boaz, Noel Two sites with surface remains were investigated in the Trnovo area on 10 July 1999. Two partial skeletons were recovered at the site of Borovci, one with a gunshot wound to the head. One skeletonized body was recovered from the site of Krčevina. Place of Exhumation: Trnovo Exhumation Site: Borovci, Krčevina Date of Exhumation: 10 June 1999 Minimum Number of Exhumed Individuals: 003